English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6x square- 11x square -4=0

-1/2 = -2

2006-11-12 13:05:18 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

FIRST PROBLEM:

6x ² - 11x ² - 4 = 0
-5x ² = 4
x ² = -4/5
x = √ (-1 * 4/5) = i * ±2 / √5 = ± 2i / √5

SECOND PROBLEM:

-1/2 does not equal -2 so I assume you made a typo on this one

NRT

2006-11-12 13:07:28 · answer #1 · answered by New Rule Tomorrow 2 · 1 0

Hi,

If I'm understanding you correctly, you are trying to solve

6x^2 - 11x^2 - 4 = 0

-5x^2 - 4 = 0

-5x^2 = 4

x^2 = -4/5

x = +-Square root(-4/5)

x = +- (2i)/Square Root (5)

Hope that helps,

Matt

2006-11-12 21:18:44 · answer #2 · answered by Matt 3 · 0 0

6x^2 - 11x^2 - 4 = 0
-5x^2 - 4 = 0

x^2 = -4/5

x = ±√(4/5)*i

Unless you mean (6x)^2 - (11x)^2 - 4 = 0; in that case

36x^2 - 121x^2 - 4 = 0 -85x^2 - 4 = 0

x^2 = 4/85, x = ±√(4/85)*i

2006-11-12 21:13:53 · answer #3 · answered by gp4rts 7 · 0 0

so: -5x sqrd = 4, x sqrd = -4/5, x = SqRt of -4/5, or i * SqRt of 4/5,

am i missing something?

2006-11-12 21:11:06 · answer #4 · answered by gggjoob 5 · 0 0

fedest.com, questions and answers